New method to produce equine antirabies immunoglobulin F(ab′)2fragments from crude plasma in high quality and yield - Sukanda Kittipongwarakarn (2018)
Rabies is still a major cause of human deaths in several developing countries. According to the World Health Organization, administration of antirabies serum or antirabies immunoglobulin is recommended for patients who have experienced a category-III exposure to rabies. Improvement of antirabies immunoglobulin production is required to enhance safety and efficacy of the products. In this paper, a new method to produce equine antirabies immunoglobulin F(ab′) 2 fragments from crude plasma is proposed. First, protein G affinity chromatography was used to purify IgG from equine plasma. Moreover, purification of IgG was shown to facilitate its digestion by pepsin. Compared to the direct digestion of crude plasma, a lower amount of pepsin and a shorter digestion time were required to completely digest the purified IgG to F(ab′) 2 . Complete digestion of purified IgG to F(ab′) 2 was achieved at a pepsin/IgG (w/w) ratio of 5:45 with preservation of structure and potency. Finally, purification of F(ab′) 2 was accomplished by a combination of protein A affinity chromatography and ultrafiltration with a 50-kDa nominal molecular weight cut-off membrane. The new process resulted in 68.9 ± 0.6 (%) total recovery of F(ab′) 2 and a F(ab′) 2 product of high potency. © 2011 Elsevier B.V. All rights reserved.